A Map of Misreading. - Li, Christina; TENT., Rotterdam (Rotterdam : Willem de Kooning Academy, 2012)
Brekke, Lars ; Clive, Edward ; Cook, Edmund ; de Oliveira, Catarina ; Fawcett, Jane ; Fibbe, Toon ; Markhus, Frode ; Meana, Fran ; Oler, Anouchka ; Roberts, Kirsty ; Unal ; Deniz
TENT, Rotterdam, 7 July - 19 August, 2012
kunstcatalogus